Can visible signs predict concussion diagnosis in the National Hockey League? - Echemendia, R. J.; Bruce, J. M.; Meeuwisse, W.; Hutchison, M. G.; Comper, P.; Aubry, M. (British Journal of Sports Medicine, 2018)
Background: Early identification and evaluation of concussions is critical. We examined the utility of using visible signs (VS) of concussion in predicting subsequent diagnosis of concussion in NHL players.